عناية الصحابة رضي الله عنهم بسياق المقام ومنهجهم في نقله وتأمينه - صحيح البخاري أنموذجا - ربوزي, سمير (جامعة الوادي - University of Eloued, 2021)
شغلَ سياق المقام العلماء والباحثين قديما وحديثا، بمختلف أطيافهم وتخصصاتهم، ولاسيما في عصرنا هذا؛ حيث أضحت فكرة المقام محورا مركزيا لدى أكثر الباحثين في علوم اللغة، وبخاصة المشتغلين بعلم الدلالة، وتحليل الخطاب. وإذ نلاحظ أنّ كمّا هائلا من الدراسات والأبحاث اشتغل أصحابُه بدراسة فكرة المقام، وحاجة فهم الخطاب النبوي إليها، وتجلّيات ذلك في مصنّفات علماء اللغة والشريعة، فإنّ جانبا مهمّا من جوانب هذا الموضوع لا يزال في حاجة إلى من يلتفت إليه، ويعطيه حقّه من العناية والدراسة؛ هو جهود الصحابة في نقل جميع عناصر السياق المقامي التي حفّت أحاديث النبي، ومنهجهم الفريد في انتخابها وتأمينها. لأجل ذلك نشأت الرغبة في كتابة هذه الورقة. Abstract : Context of situation has been a concern among scholars and researchers of different specialities in the past and present, especially nowadays. In fact, the idea of situation has become a central focus of most researchers in language sciences, especially those studying semantics and discourse analysis. While we notice that researchers undertook a huge amount of studies and did research on the idea of situation, and the need of it to understand the prophetic discourse, and its different manifestations in works of Sharia scholars; an important aspect of this topic has remained in need of someone who gets down to it and deal with it appropriately in terms of study and attention. This aspect is the efforts of the Companions in conveying all the elements of context of situation found in the Messenger hadiths, and their unique methodology in choosing them and safeguarding them. The desire for writing this paper emerged for this reason
مقال
Keywords: عناية؛ الصحابة؛ سياق المقام؛ منهج؛ نقل؛ أحاديث الرسول